1999
DOI: 10.1074/jbc.274.5.2794
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Cannabinoid CB1 Receptor Is a 2-Arachidonoylglycerol Receptor

Abstract: An endogenous cannabimimetic molecule, 2-arachidonoylglycerol, induces a rapid, transient increase in intracellular free Ca 2؉ concentrations in NG108 -15 cells through a cannabinoid CB1 receptor-dependent mechanism. We examined the activities of 24 relevant compounds (2-arachidonoylglycerol, its structural analogues, and several synthetic cannabinoids). We found that 2-arachidonoylglycerol is the most potent compound examined so far: its activity was detectable from as low as 0.3 nM, and the maximal response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
111
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(117 citation statements)
references
References 33 publications
(22 reference statements)
5
111
0
1
Order By: Relevance
“…1) and had initiated an evaluation of its biological properties before the completion of the work described now (14,15). Independently, Sugiura et al had prepared this compound also (16) and Suhara et al had examined its effects on Ca 2ϩ levels in cells (17). The availability of synthetic noladin ether made possible a direct comparison with the natural product.…”
Section: Resultsmentioning
confidence: 99%
“…1) and had initiated an evaluation of its biological properties before the completion of the work described now (14,15). Independently, Sugiura et al had prepared this compound also (16) and Suhara et al had examined its effects on Ca 2ϩ levels in cells (17). The availability of synthetic noladin ether made possible a direct comparison with the natural product.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 2-AG was shown to be present in vivo at levels several orders of magnitude higher than the other known endocannabinoid, AEA (2)(3)(4). Accumulating evidence supports assertions that 2-AG serves as a physiologically relevant cannabinoid receptor ligand, occupying a central role within the endogenous cannabinoid system (5,6). Therefore, the identification and characterization of enzymes capable of metabolizing this lipid mediator should aid in the elucidation of mechanisms by which cannabinoid tone is modulated in vivo.…”
mentioning
confidence: 97%
“…[9][10][11] 2-AG elicits a variety of biological responses in various nervous tissues and cells. 15) For example, 2-AG induced a Ca 2ϩ transient in NG108-15 cells, 9,10) the inhibition of longterm potentiation 16) and the inhibition of synaptic transmission 17) in rat hippocampal slices, and the inhibition of voltage-gated Ca 2ϩ channels and the activation of inwardly rectifying K ϩ channels in rat sympathetic neurons 18) via CB1 receptor-dependent mechanisms. On the other hand, not much information is available concerning the effects of 2-AG on inflammatory cells and immune-competent cells which express the CB2 receptor.…”
mentioning
confidence: 99%
“…7,8) Previously, we investigated in detail the structure-activity relationship of cannabinoid receptor ligands and found that 2-AG is the most efficacious agonist among the various structural analogs and homologs thus far examined. [9][10][11] Importantly, 2-AG acted as a full agonist toward these cannabinoid receptors in various assay systems, [9][10][11][12][13][14] whereas anandamide often acted as a partial agonist. Based on these experimental results, we proposed that 2-AG, rather than anandamide, is the true natural ligand for the cannabinoid receptors.…”
mentioning
confidence: 99%